Intraoperative embolism or type I hypersensitivity reaction to gelofusine® - Ramkrishnan, Aishwarya; V V, Meenakshi; -, Karthikeyan (Indian Journal of Case Reports, 2019)
Despite rare reports of Type I Hypersensitivity reactions (anaphylaxis) to colloid plasma expanders, they find wide application during resuscitation and major surgeries. We present the case of a possible Type I hypersensitivity reaction to Gelofusine® in a 42-year-old female patient during oncological surgery. The delayed manifestation caused some diagnostic confusion with an embolic event. The patient was symptomatically treated and the rest of the surgery was completed uneventfully. A high index of suspicion is vital for prompt identification and treatment of anaphylaxis.